Exploring the Role of Primary Healthcare Workers in the Detection of Congenital Hearing Loss : a Survey-Based Study in Lhokseumawe - Varry, Rezza; Ammara, Cut Balqis; Zachreini, Indra (GALENICAL : Jurnal Kedokteran dan Kesehatan Mahasiswa Malikussaleh, 2025)
Healthcare workers’ behavior plays a crucial role in the success of early detection of congenital hearing loss. This behavior is influenced by their knowledge, attitudes, and practices in clinical settings. This study aims to evaluate the level of healthcare workers’ behavior in primary care services in Lhokseumawe City in detecting congenital hearing loss. Research Objective: To assess the level of healthcare workers’ behavior in the early detection of congenital hearing loss in primary care services in Lhokseumawe City. Research Method: This is a descriptive analytic study with a cross-sectional design. The research was conducted over one year (July 2023 – June 2024). The study sample consisted of healthcare workers who met the inclusion criteria: working as general practitioners, nurses, or midwives in primary care services in Lhokseumawe City, aged 20 years and above, and willing to participate in the study. The exclusion criterion was incomplete responses to the questionnaire. Research Results: The majority of respondents were female (89.93%), in the productive age group, and predominantly midwives (66%). About 48% of respondents knew that the ideal age for diagnosing congenital hearing loss is 3 months, and 50% knew that the ideal time for intervention is 6 months. Most respondents demonstrated a positive attitude toward the importance of early detection, and 100% were willing to make referrals. In practice, 95% conducted family history taking, 70% performed hearing screening tests, and 79% examined ear abnormalities in infants or children. Conclusion: The level of healthcare workers’ behavior regarding early detection of congenital hearing loss reflects generally good attitudes and practices; however, there are still gaps in knowledge related to the ideal timing of diagnosis and intervention. Training interventions and the provision of screening tools need to be improved to optimize the role of primary care services in early detection programs for congenital hearing loss.